SISTEM INFORMASI KEMATIAN IBU TERINTEGRASI DALAM PENCATATAN DAN PELAPORAN KEPENDUDUKAN SUMATERA SELATAN - Ekowati Retnaningsih; Muhammad Zulkarnaen; Irmitati Irmitati (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Improve health status of mother represent the agreement of a world of decanted in target of development millenium ( MDGS). South Sumatra is not merely having height of Martenal Mortality Rate (MMR) but also information system of mother death which not yet good. The maternal mortality rate in South Sumatra at year 2004 ( SUSENAS) is 467 while national of MMR is 307 per 100.000 birth live. Pursuant to report which step into the Public Health Service of Provinsi of South Sumatra at year 2004 noted is a mother death only 60 people from totalizeing birth of a number of 167.852 people (36 per 100.000). To know the MMR by a survey require the very big expense, so that very difficult to get MMR routinely every year. Though, to know the cause of height of MMR and planning program to intervention, we have to have the individual data about death of mother and MMR. For that have to be searched the opportunity obtain to get the MMR by system development available information in this time. This research was consisted by 2 phase that is 1) phase of information gathering to obtain;get the data exhaustively by research qualitative about informan of key and information system death there was and its execution in society and 2) phase of system development of information of mother death. Research location in 3 regency / town, that is: 1) Banyu Asin district, 2) OKI district, and 3) Palembang city.The result was inferential: 1) key Informan of about death occurence in society was Chief RT, 2) This time there was legal information system of death there have in system of record-keeping and vital occurence reporting of resident 3) Have been developed a information system integrated mother death with the record-keeping and vital occurence reporting of resident with the system of cros chek of band of health institution and also provided with the existence of institute will called death Committee at level of provinsi come up to the subdistrict level. Suggested to local government and on duty related/relevant institution to conduct the test-drive of information system which have been yielded by researcher.